Assessing the impact of obesity on surgical quality outcomes among patients undergoing hysterectomy for benign, non-urgent indications. (July 2022) - Cybulsky, Marta; Murji, Ally; Sunderji, Zahra; Shapiro, Jodi; Elliott, Cara; Shirreff, Lindsay
Highlights: Obese patients did not have more complications, ED visits or hospital readmissions. BMI class was not independently associated with surgical quality outcomes. Hysterectomy can be performed safely in overweight and obese patients. Abstract: Objective: To evaluate the impact of body mass index (BMI) on surgical quality metrics for patients undergoing benign, non-urgent hysterectomy. Study design: A multicentre, retrospective review at 7 hospitals in Ontario, Canada (4 academic, 3 community) was conducted. Patients undergoing hysterectomy from July 2016 to June 2019 were included. Hysterectomies for premalignant, malignant and emergency indications were excluded. The primary outcome was a composite of any complication or readmission. Secondary outcomes were grade 2 or greater complication, postoperative emergency department (ED) visit, hospital readmission, operative time (ORT) and estimated blood loss (EBL). Patient characteristics (age, ASA class, preoperative diagnoses, preoperative anemia, prior surgeries), surgical factors (endometriosis, adhesions, hysterectomy route, uterine weight, concomitant procedures, ORT, EBL) and surgeon characteristics (volume, fellowship/generalist training, academic/community hospital) were recorded along with complications, hospital readmissions and ED visits. Outcomes were evaluated using logistic regression and log-regression linear analysis grouping patients by BMI category (normal, overweight, obesity class 1, 2, and 3) and by hysterectomy route (abdominal, laparoscopic, and vaginal). Results: 2528 hysterectomies were performed by 67 surgeons. 828 (33%) patients had a normal BMI, 889 (35%) were overweight. 500 (20%) patients had a BMI corresponding to obesity class 1, 205 (8%) class 2 and 106 (4%) class 3. Obese patients had higher ASA class (p <.001) and more prior surgeries (p <.001) compared to patients with normal BMI. Those with class 2 and 3 obesity were younger (p <.001), had greater uterine weight (p <.001) and more intra-operative adhesions (p <.001). After controlling for covariates, there were no differences in the odds of the primary or secondary outcomes, with the exception of patients with class 2 obesity who underwent vaginal hysterectomy. They had 9.1% (11 min) significantly longer ORT (0.091, 95% CI 0.002-0.18, p <.05) and patients with an overweight BMI who underwent vaginal hysterectomy had 28 ml significantly less EBL (−0.154, 95% CI −0.26 to -0.05, p <.01) compared to patients with normal BMI. Conclusion: BMI was not independently associated with surgical quality outcomes in patients undergoing hysterectomy for benign, non-urgent indications. Abdominal, laparoscopic, and vaginal hysterectomy can be performed safely in overweight and obese patients.